DECREASING TREND OF SAMOSIR PANORUSAN GOAT POPULATION IN PANGURURAN SUB DISTRICT: CAUSING FACTORS - Andriani Manik; Edhy Mirwandhono; Nurzainah Ginting; Hasnudi .; Iskandar Sembiring (Universitas Sumatera Utara, 2018)
This research was conducted at the people’s farm in Pangururan sub-district, Samosir district. This study aims to determine the factors that affect the reduction rate of Panorusan goat population. The method used was multiple linier regression analysis with variabel limitations, i.e. animal feed quality, quantity of field grass, and goat sales to other areas. This research was conducted by asking directly to the breeder and giving a randomly selected questionnaire. The total of 55 goat breeders are divided into 2-3 breeders/village. From the research it was known that the dominant factor that causes the rate of reduction in goat Panorusan Samosir population was goat sales to other areas.